Stability of 19-norandrosterone and 19-noretiocholanolone glucuronide in urine under various storage conditions - Van Der Merwe, P.J. & Grobbelaar, E. (South African journal of sports medicine, 2003)
The International Olympic Committee (IOC) has ruled that 19-norandrosterone should be quantified if present in low concentrations in urine of sport competitors. The question, however, is how stable is 19-norandrosterone in urine. In the light of this IOC ruling it is therefore important to know if the concentration of 19-norandrosterone can change during the transportation process of urine samples to the laboratory or during the handling and storage of the samples in the laboratory.